A high fidelity cost efficient tensorial method based on combined POD-HOSVD reduced order model of flow field. Issue 4 (4th July 2018) - Moayyedi, Mohammad Kazem; Najaf beygi, Milad
ABSTRACT: Computation time and data storage is a significant challenge in every calculation process. Increasing computational speed by upgrading hardware and the introduction of new software are some of the techniques to overcome this challenge. One of the most interesting methods for fast computations is the reduced order frameworks. In this study, the aerodynamic coefficients of the NACA0012 airfoil in subsonic and supersonic flows have been reconstructed and estimated by a cost-efficient form of combined proper orthogonal decomposition–high-order singular value decomposition (POD-HOSVD) scheme. The initial data ensemble contains some members related to the variations of the angle of attack and Mach number. To reduce the computation time, the structure of the standard combined POD-HOSVD approach has been changed to a cost-efficient format. The present method is a grid independent formulation of standard combined POD-HOSVD for the fields with a large number of elements and several effective variables. Results indicate more than 90 percent reduction in the calculation time compares with computational fluid dynamics and standard combined POD-HOSVD methods for a subsonic flow field.